Past deformations of "Brezhnevian stagnation" in Lithuanian cinema and TV fiction films (1968-1980) - Lina Kaminskaitė-Jančorienė (Lietuvos Istorijos Studijos)
The objective of this work is to identify collective memory shapes in Lithuanian fiction TV and cinema film during the Brezhnevian period (1968-1980). According to new popular theoretical approaches, this work analyses the specific source of history—fiction film—so this research brings Lithuanian fiction film up-to-date with usual resources of history.